The Use of Gamification in EFL Teaching: Student Engagement and Learning Outcomes - Ibrahim Mustafa Almahde Alfaqi, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
Gamification has gained momentum in education, offering a fresh approach to teaching English as a Foreign Language (EFL). This study examines how gamification impacts student engagement and learning outcomes in EFL classrooms. A mixed-methods approach was used, combining quantitative assessments and qualitative feedback. Results showed significant improvement in student motivation and language proficiency. Students reported enjoying learning, while teachers observed more participation and collaboration. The findings suggest that gamification can revolutionize EFL teaching when applied thoughtfully. It brings excitement and measurable results to the classroom. This paper provides practical insights for educators and researchers.